2022
DOI: 10.1177/19253621221119081
|View full text |Cite
|
Sign up to set email alerts
|

Visceral Microscopic Pattern From Suicidal Ingestion of Professional Lysoform® With Delayed Death

Abstract: Lysoform® in the formulation of professional detergent is widely used in several fields, whereas its suicidal ingestion is an unusual occurrence. Therefore, the biological signs of this fatal poisoning remain unclear and elusive, similarly to the histological lesions induced by its main constituent, which is benzalkonium chloride (BZK). Furthermore, since all the deaths that has been reported in the literature occurred immediately, microscopic pictures of BZK lethal toxicity in subjects with prolonged survival… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 15 publications
0
11
0
Order By: Relevance
“…This is correct from a procedural point of view, but it should never be forgotten that toxic substances are such as they are able to exert their damaging action directly or indirectly on biological tissues, leaving signs that only microscopic examination can bring out and correctly characterize in the pathophysiological reconstruction of the death event. From this derives the need to always associate histopathological with toxicological analysis, because, in addition to providing direct confirmation of the harmful effects produced by the substance, it can also bring to light specific peculiarities not yet known or rarely reported in literature, such as cardiac hemorrhage associated with the ingestion of caustic substances 39,40 . This becomes even more crucial in cases of more or less prolonged survival periods after exposure to substances of toxicological interest, which, in the forensic field, are still poorly described, because, most of the times, the lethal event is immediate.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is correct from a procedural point of view, but it should never be forgotten that toxic substances are such as they are able to exert their damaging action directly or indirectly on biological tissues, leaving signs that only microscopic examination can bring out and correctly characterize in the pathophysiological reconstruction of the death event. From this derives the need to always associate histopathological with toxicological analysis, because, in addition to providing direct confirmation of the harmful effects produced by the substance, it can also bring to light specific peculiarities not yet known or rarely reported in literature, such as cardiac hemorrhage associated with the ingestion of caustic substances 39,40 . This becomes even more crucial in cases of more or less prolonged survival periods after exposure to substances of toxicological interest, which, in the forensic field, are still poorly described, because, most of the times, the lethal event is immediate.…”
Section: Discussionmentioning
confidence: 99%
“…From this derives the need to always associate histopathological with toxicological analysis, because, in addition to providing direct confirmation of the harmful effects produced by the substance, it can also bring to light specific peculiarities not yet known or rarely reported in literature, such as cardiac hemorrhage associated with the ingestion of caustic substances. 39,40 This becomes even more crucial in cases of more or less prolonged survival periods after exposure to substances of toxicological interest, which, in the forensic field, are still poorly described, because, most of the times, the lethal event is immediate. In this context, PQ deaths are no exception, and the histological findings that emerge may be of clinical relevance in optimizing the treatment and management of these patients.…”
Section: Discussionmentioning
confidence: 99%
“…In a review of cases of both adults [ 16 , 43 , 44 ] and children [ 45 , 46 , 47 , 48 , 49 ] who survived the ingestion of BAC solutions, strictures were described in only a few neonatal cases [ 48 ]. Therefore, the positive outcome in our patient and the management or nature of the substance involved are likely not directly nor causally related.…”
Section: Discussionmentioning
confidence: 99%
“…The rapid development of acute respiratory distress in this patient may be related to laryngeal edema and BAC-induced bronchoconstriction through the release of mediators from mast cells and the stimulation of cholinergic receptors [ 16 ]. The mechanisms of lung toxicity have been extensively studied via animal models [ 18 ], cell culture investigations [ 12 ], and forensic reports [ 16 ], resulting in the characterization of BAC-induced lung injury. Based on these data and previously reported cases [ 43 , 46 , 47 , 48 , 49 ], we concluded that our patient developed chemical pneumonitis because he aspirated the BAC solution.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation